Algebra: A Combined Approach (4th Edition)

Published by Pearson
ISBN 10: 0321726391
ISBN 13: 978-0-32172-639-1

Chapter 5 - Section 5.5 - Multiplying Polynomials - Exercise Set: 86

Answer

$-8x+6$

Work Step by Step

$(2x-1)-(10x-7)=2x-1-10x-(-7)=2x-1-10x+7=(2-10)x-1+7=(-8)x+6=-8x+6$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.